Awareness of cross-infection and its control measures among patients attending a tertiary dental hospital in Nepal - Pandey, Sushant; Shrestha, Utsav; Dahait, Regina (Birat Journal of Health Sciences, 2022)
Introduction: Dental procedures frequently lead to exposure to blood and saliva which can carry a variety of pathogens. Aerosols produced during dental treatment procedures can further facilitate the transmission of these infectious agents. It is equally important for the patients to be aware of cross-infection and measures taken to prevent it in a dental setting. Objectives: The main objective of this study was to assess the awareness of cross-infection and its control measures among patients attending College of Dental Surgery, B.P. Koirala Institute of Health Sciences (BPKIHS). Methodology: A cross-sectional study was carried out among 362 patients who attended College of Dental Surgery, BPKIHS. Data was collected by administering a questionnaire that consisted of 4 questions intended to collect sociodemographic information and 10 close-ended questions designed to assess awareness of cross-infection and its control measures. The data was entered and analyzed using SPSS® software for Windows®. Results: The majority of the participants were aware that there was a chance for an infection to be transmitted from a dentist to a patient (82%), from a patient to a dentist (80.4%), and in between patients attending the same dental clinic (70%). Most of the participants considered wearing gloves (94.4%) and facemask (86%) by the dentist to be important. Only 40.3% of participants were aware of better methods of sterilization other than boiling in water. Awareness was higher among participants with higher education (p<0.05). Conclusion: The majority of the participants were aware that there was a chance for an infection to be transmitted from a dentist to a patient. However, the dental healthcare professionals should educate people about the possible risks of cross-infection and the importance of infection-control practices in dental clinics. Modern mass media and social media can be used to spread awareness to a large segment of the population.